Enhancing CO2 mass transfer in large scale algal raceway ponds through wave generation - Middleton, William (Department of Chemical Engineering, 2025)
The commercial growth of algae in raceway ponds is limited by the availability of carbon, supplied as carbon dioxide (CO2), resulting in a linear growth rate, also described as biomass productivity, determined by the mass transfer rate. This reduces the specific growth rate of the system, as the culture cannot achieve the maximum growth rate limiting the productivity of systems. A novel system for enhancing CO2 mass transfer using slopes is being investigated by the Center for Bioprocess Engineering Research (CeBER) at the University of Cape Town. This contributes to the ongoing investigation into the use of carbon sequestering organisms as a means of producing valuable compounds. The growth rate of algae has presented a major constraint in its commercial applicability. Typically, raceway systems are limited by the available light and carbon in the system. The carbon source for autotrophic algal growth in raceways is typically atmospheric CO2. The rate at which this enters the system is based on the concentration gradient at the gas/liquid interface. The addition of slopes aims to increase the turbulence in areas of the raceway systems with low CO2 mass transfer to increase the concentration gradient across the gas/liquid interface, facilitating higher carbon input to the system. An increase in turbulence serves to both promote axial mixing in the raceway facilitating CO2 transport to the lower liquid regions and at the microscale within the liquid medium, allowing the surface renewal of liquid with low CO2 concentrations to interact with the gas/liquid interface. The slopes were designed based on weirs, which create an impediment to flow, resulting in increased turbulence downstream of the slope. A number of slope gradients and heights were investigated in prior work done (Burke, 2016; Van Der Linde, 2022). The focus of this study was to validate these previous findings conducted at laboratory scale and investigate the applicability of the scale up of the slopes at larger scales. Two raceway scales were tested: the existing 62 L raceway ponds used in earlier studies and a 1000 L raceway pond designed and commissioned for this project. At constant paddlewheel rotation, a large reduction in fluid velocity was observed on introducing the slope. Higher fluid velocities result in more turbulent flow, better mixing and reduces algae settling in areas of low fluid velocity. The effect of the lower fluid velocity was evident as the increases in algal productivity were not proportional to the increases in mass transfer. It was found that the slopes performed better in the 1000 L raceway compared to the 62 L raceway. The average fluid velocity decreased by 13 – 20 cm/s and 4 – 15 cm/s in the 62 and 1000 L raceways, respectively with the utilization of slopes, indicating that the slopes had a proportionately smaller effect on fluid velocity at a larger scale. The mass transfer coefficients (kLa) improved by 0.02 – 0.18 h-1 and 0.34 – 0.63 h-1 in the 62 and 1000 L raceways, respectively. These indicate significant improvements in CO2 mass transfer compared to the system without slopes. It was evident from the analysis that the increase in surface disturbance and therefore surface area for transfer as well as the increased turbulence in the system resulted in a net increase in CO2 mass transfer rate in the raceway systems. The growth rates of a test strain, Scenedesmus spp., was used as validation for the increased mass transfer rates, as where the carbon availability is the limiting factor during the linear growth phase, then an increase in CO2 mass transfer rate will result in a proportional increase in the growth rate of the algae. However, no significant changes to the algal productivity were seen. This suggests that light is the limiting factor during the linear growth phase, but the results of these experiments were inconclusive and remain an area of interest to be investigated further.